“Desejo que se faz magma nas entranhas": crítica feminista, linguagem subversiva e erotismo em Magma de Olga Savary - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This dissertation proposes an analysis of Olga Savary's poetry in her work Magma (1982), focusing on the use of eroticism as a form of resistance to patriarchal structures within feminist literary criticism. The main objective of this research is to analyze eroticism in the poetic work Magma as a mechanism of subversion of patriarchal norms, promoting a poetic language that challenges social conventions and affirms female autonomy and empowerment. To achieve this goal, the study examined the poetic construction of the body and erotic desire in the work, identifying them as instruments of female empowerment. Through an analysis of the poems, this dissertation seeks to understand how Savary uses subversive language to deconstruct patriarchal narratives and promote a more emancipatory view of the female body and desire. Furthermore, this study contextualizes Magma within the feminist movement, situating the work in the historical and social panorama in which it was produced. From this contextualization, it is possible to better understand the influences and impacts of Olga Savary's poetry on the Brazilian literary scene and in discussions about gender and sexuality. Finally, we conclude that her work offers a rich and multifaceted poetic vision of the female struggle for autonomy and power, contributing to the debate on Savary's place in the Brazilian modernist context and opening space for further investigations of her work from a feminist criticism perspective.
Keywords: Erotismo; Subversão; Crítica literária feminista; Magma; Olga Savary; CNPQ:: CIÊNCIAS HUMANAS